2018
DOI: 10.1177/2380084418785863
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Changes in Masticatory Performance: The Suita Study

Abstract: Introduction: Although previous studies have identified various factors related to masticatory performance, which factors affect longitudinal changes in masticatory performance have not been clarified. Objectives: We aimed to clarify factors involved in changes to masticatory performance and construct models from factors related to masticatory performance in a longitudinal study of a general urban population in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 27 publications
11
56
0
2
Order By: Relevance
“…Declined masticatory function is related to poor nutrition, resulting in poor systemic health conditions and low quality of life [11][12][13][14][15][16][17][18]20]. Particularly in patients with maxillofacial defects after surgical resection due to oral, head, and neck cancer, it should be the first step to resolve masticatory issues for oral and social rehabilitation [3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Declined masticatory function is related to poor nutrition, resulting in poor systemic health conditions and low quality of life [11][12][13][14][15][16][17][18]20]. Particularly in patients with maxillofacial defects after surgical resection due to oral, head, and neck cancer, it should be the first step to resolve masticatory issues for oral and social rehabilitation [3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MOF is strongly related to age, condition of occulsal support [3,27], and prosthetic intervention [9,28]. Although the effect of multicollinearity between these predictor variables, especially age, MOF, and the number of occlusal support, on the statistical results were considered, previous studies also assessed the factors associated with masticatory performance [12][13][14][16][17][18] and showed significant correlations with these factors [12][13][14]17,18]. Accordingly, we decided to use these variables as predictor variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related question is the direction of the change: most often, spontaneous evolution, either gradual or sudden, tends toward a worsening of the occlusion conditions of mastication; a gradual or sudden change for the better is expected after therapeutic interventions. Apart from saliva, which must be of adequate quality and quantity, two factors seem to affect the extent of adaptation: (i) number of functional teeth and (ii) masticatory forces (Hatch et al, 2000;Kosaka et al, 2018). The presence of enough functional interarch posterior tooth-to-tooth contacts as indicated by the PFU concept is a determining factor (van der Bilt, 2011; Tanaka and Shiga, 2018).…”
Section: Adaptation Of Mastication To Changes In Functional Occlusionmentioning
confidence: 99%
“…Very advanced age is another possible factor in neuromuscular system decline (Osterberg et al, 1996). However, several studies have shown that outside extreme vital decline, elderly subjects were able to adapt to the age-induced changes provided there were not too many interfering problems (Peyron et al, 2017), and particularly if they had a sufficient number of PFUs (Kohyama et al, 2003;Kosaka et al, 2018). However, the effect of age is often one factor among many, where the specific role of any single one is difficult to specify.…”
Section: Adaptation Of Mastication To Changes In Functional Occlusionmentioning
confidence: 99%